RANCANG BANGUN SISTEM INFORMASI PENERIMAAN KARYAWAN BARU BERBASIS WEB PADA PT. SATRIA ANTARAN PRIMA TBK - Masruri Masruri; Achmad Raizaldi; Agus Budiyantara (STMIK Widuri Jakarta, 2024)
The new employee recruitment system that runs at PT. Satria Antaran Prima Tbk is still a convention where applicants must come directly submit their application files, causing several problems including the application selection process takes a long time because it is done manually, there is often damage or loss of application files because the data is stored in archive form in a storage cabinet, the psychological test process takes a long time because it is done manually using paper and checking the psychological test results is done manually. The purpose of this research is to know the system that is running, analyze and design the system according to system requirements. This study uses a descriptive method with a qualitative approach where the data obtained directly through interviews, observation, literature and documentation. The proposed system design uses Data Flow Diagrams (DFD), database design uses Entity Relationship Diagrams (ERD), interface design on the proposed system and system testing using Blackbox Testing and system implementation. The result of this research is to design a web-based new employee recruitment information system that can be implemented at PT. Satria Antaran Prima Tbk to provide alternative solutions to existing problems so that the hiring process for new employees can run effectively and efficiently